The Relationship Between Severity of Periodontitis With the Degree of Atherosclerosis in Ischemic Stroke Patients - Tikalaka, Elisabeth Romana; Husni, Amin; -, Retnaningsih; Tugasworo, Dodik; Hartono, Jimmy Eko Budi; Rahmawati, Maria Belladonna; Puspitasari, Iva (Diponegoro International Medical Journal, 2021)
AbstractBackground : Periodontal diseases affect up to 80% of the global population. Periodontitis is a long-term inflammatory disease that affects the soft and hard tissues around the teeth. It may also play a role in the pathogenesis of atheroma formation and is associated with cerebrovascular disease. The Carotid Intima Media Thickness (CIMT) is a good marker for detecting early and progressive atherosclerosis. Several hypotheses link chronic infectious diseases, including periodontal tissue disease, to the atherosclerosis process and are risk factors for stroke.Objective : To determine the relationship between the severity of periodontitis and the degree of atherosclerosis in ischemic stroke.Methods : This is an analytic observational study with a case-control approach. Subjects were ischemic stroke patients with inclusion criteria. Analyzed the severity of periodontitis with Miller’s Mobility Index (MMI), the degree of progression of atherosclerosis assessed by measuring the CIMT using an ultrasound device or B mode to detect the presence and progression of atherosclerosis.Results : 54 subjects with a mean age were 63,43 ± 7,19 years, and the dominant sex was male. There was a significant relationship between severity of periodontitis  ( P : 0,011, OR : 3,425, CI 95% 1,332-8,807) and type of profile lipid triglyceride ( P : 0,027, OR : 6,840, CI 95% 1,242-37,676)  to Carotid intima media thickness.Conclusion :  There is an association between the severity of periodontitis and the degree of atherosclerosis. Severe periodontitis is related to the increases of CIMT, which is a marker of atherosclerosis, a risk factor for stroke.